P-043 Feasibility of a Multicenter, Collaborative, Longitudinal, Quality Improvement Learning Health System for Adult IBD Care. (February 2017) - Melmed, Gil; McCutcheon Adams, Kelly; Bray, Harry; Caron, Jessica; Deitch, Joshua; Hirschhorn, Gary; Jones, Michael; Long, Millie; Lum, Donald; Rubin, David; Shah, Samir,; Hou, Jason; et al.
Abstract : Background: There is significant variation in processes and outcomes of care for patients with chronic inflammatory bowel diseases (IBD), suggesting poor quality of care. Improved quality of care can be facilitated through patient-centered learning health systems, process improvement methods, and multicenter collaborative models such as the Breakthrough Series (BTS) Collaborative developed at the Institute for Healthcare Improvement (IHI). We piloted a learning health system of clinical practices caring for adults with IBD, and assessed the feasibility of a BTS innovation collaborative focused on improving the delivery of urgent IBD care. Methods: Following IHI methodology, a focus topic (Improving delivery of urgent IBD care) was selected, and a charter was drafted for an 18 months BTS collaborative. Experts and faculty (5 physicians, 3 patients, and a quality improvement advisor) identified primary and secondary drivers of urgent IBD care delivery, and a package of "change ideas" were created. Key process and outcome measures were established based on previously published IBD outcome metrics. Improvement teams comprised of a physician, nurse and/or coordinator at each of ten IBD-focused clinical sites (6 university-based, 4 community) attended three 2-days in-person learning sessions marking the beginning, middle, and end of the collaborative. Sites each selected 3 to 5 change ideas most relevant to their settings, and learned quality improvement methods centered on the Model for Improvement. Standardized patient-reported measures were collected during patient-visits, and sites submitted monthly reports detailing their progress. Collaborative-wide coached monthly webinars were held to track and review progress using statistical process control charts, and to facilitate sharing of ideas and best practices. Results: Four primary drivers of improving urgent IBD care delivery were identified: (1) Patients are activated, well-informed, and engaged in self-management and care planning (2) Care is available and accessible when needed (3) Care is collaborative, evidence-based, and consistent and (4) Care processes are patient-centered, with the right staff and resources. Nineteen "change ideas" related to these drivers were developed, and each site selected 3 to 5 changes to test. These included reserved "urgent care" ambulatory slots, development of urgent care nurse hotlines, tracking and improving telephone callback time, creation of patient education materials and website enhancements specifically regarding urgent care, telehealth for urgent care, restructuring mid-level provider time to accommodate or triage urgent patients, addition of intravenous hydration capabilities in the clinic, and education of local emergency room physicians. Patient-reported measures were collected at over 5500 discrete patient visits, including data on emergency room utilization, hospitalization, steroid and narcotic use, disease activity, and satisfaction with urgent care experiences. All teams were represented at each learning session, and participation on monthly webinars ranged from 90% to 100%. Conclusions: A learning health system for adult IBD care in which clinical teams engage in systematic, collaborative, longitudinal quality improvement efforts is feasible. Process and outcome measures for adult IBD care can be reported by patients, minimizing practice burden for data collection. Efforts to demonstrate the feasibility of expanding the learning health system to varied healthcare settings, use of electronic data capture, electronic health record integration, and use of standardized care pathways are ongoing.